The Role of the Government in Promoting Digital Skills Development among the Elderly: A Case Study of Wang Subdistrict Administrative Organization, Tha Chana District, Surat Thani Province - Patthanadachakul, Natthanicha; Duangrit, Thanyaret; Amsuk, Ratchaphon (Journal of Public Administration Chiang Rai Rajabhat University, 2026)
This research aimed to: 1. Examine the role of the government sector in promoting the Development of digital skills among older adults in the Wang Subdistrict Administrative Organization; and 2. Explore the attitudes, perspectives, and experiences of older adults in the Wang Subdistrict Administrative Organization, Tha Chana District, Surat Thani Province, regarding the use of digital technology. A qualitative research method was employed, using in-depth interviews with four personnel from the Wang Subdistrict Administrative Organization and the Wang Subdistrict Health Promoting Hospital, as well as a focus group discussion with eight older adults. The findings revealed that: 1) The Wang Subdistrict Administrative Organization, as a relevant governmental body, plays a key role in promoting the development of digital skills among older in its jurisdiction because it is responsible for providing various public services to them. Addressing challenges in promoting digital skill development for older adults requires collaboration with other government sectors, particularly the private sector, as well as the general public, in order to reach shared agreements and mutual needs. The organization has incorporated digital technology systems to enhance its administrative processes. 2) Regarding the attitudes, perspectives, and experiences of older adults, the implementation of digital technology in the operational processes of the Wang Subdistrict Administrative Organization has enabled older adults and the general public to gain better access to services. The organization has adjusted both its internal and external services procedures, aligning with concepts related to the development of the government’s digital systems and the notion of New Public management. This includes improvements in administrative management through the full integration of digital technology in public administration and public service delivery, as well as the integration of government databases. These efforts aim to create balance and enhance management systems, elevate public services toward excellence, and respond to service recipients’ needs with convenience, speed, and transparency